High Frequency Occult Hepatitis B Virus Infection Detected in Non-Resolved Donations Suggests the Requirement of Anti-HBc Test in Blood Donors in Southern China - Ye, Xianlin; Zhao, Yu; Li, Ran; Li, Tong; Zheng, Xin; Xiong, Wen; Zeng, Jinfeng; Xu, Min; Chen, Limin (Frontiers in Immunology, 2021)
Background: Most Chinese Blood Centers adopted minipool (MP) nucleic acid testing (NAT) for HBV screening due to high cost of Individual donation (ID) NAT, and different proportions of MP-reactive but ID-nonreactive donations (MP+/ID−, defined as non-resolved donations) have been observed during daily donor screening process. Some of these non-resolved donations are occult HBV infections(OBIs) which pose potential risk of HBV transmission if they are not deferred. This study is aimed to further analyze these non-resolved donations. Methods: The non-resolved plasma samples were further analyzed by serological tests and various HBV DNA amplification assays including quantitative PCR (qPCR) and nested PCR amplifying the basic core and pre-core promotor regions (BCP/PC; 295 base pairs) and HBsAg (S) region (496 base pairs). Molecular characterizations of HBV DNA+ non-resolved samples were determined by sequencing analysis. Results: Of 17226 MPs from 103,356 sero-negative blood donations, 98 MPs were detected reactive for HBV. 56 out of these 98 (57.1%) reactive MPs were resolved as HBV DNA+, but the remaining 42 pools (42.9%, 252 donations) were left non-resolved with a high rate (53.2%) of anti-HBc+. Surprisingly, among 42 non-resolved MPs, 17 contained one donation identified as OBIs by alternative NAT assays. Sequence analysis on HBV DNAs extracted from these OBI donations showed some key mutations in S region that may lead to failure in HBsAg detection and vaccine escape. Conclusion: 53.2% of the non-resolved donations were anti-HBc+ and OBIs were identified in 40.5% of these non-resolved pools. Therefore, non-resolved donations with anti-HBc+ might pose potential risk for HBV transmission. Our present analysis indicates that anti-HBc testing in non-resolved donations should be used to identify OBIs in order to further increase blood safety in China.